Penanaman Nilai Moral Anak Usia Dini Melalui Pengembangan Media Pembelajaran Paper Show Di RA Al Ishlah Sumurgung - Nurul Farida; Nurlaili Dina Hafni (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
The aims of this study were (1) to describe the validity of the Paper Show learning media as a moral instillation in RA Al Ishlah, Sumurgung Village, Montong District, Tuban Regency. (2) To demonstrate the practicality of Paper Show learning media as moral cultivation at RA Al Ishlah, Sumurgung Village, Montong District, Tuban Regency. (3) To demonstrate the effectiveness of the Paper Show learning media as a moral inculcation at RA Al Ishlah, Sumurgung Village, Montong District, Tuban Regency, 2021/2022 Academic Year.This research uses the research and development method of R&D (Research and Development) with a 4D model. Validity tests were carried out on Ahi Media Validators, Material Expert Validators, Class Teachers, Users. Data collection in this study used Observations, Questionnaires, Documentation.Based on the validity test data, the Paper Show meets the very valid or very feasible category. Validation obtained by material expert data gets a percentage of 92.5%. Media expert data validation gets a percentage of 82.5%. The average validation results get a percentage of 87.5%. By calculating the percentage, the Paper Show is very feasible to use. Meanwhile, based on the level of practicality of the developed Paper Show, it was assessed from the student response questionnaire that it received a percentage of 91.9% and the teacher's response questionnaire received a percentage of 93.3%, with very good criteria. This shows that Paper Show is practically used in the learning process. Meanwhile, based on the effectiveness of the Paper Show from the observation sheet of children's learning assessment of the media developed, it was obtained from the pre-test and post-test results with the Gain normality test obtaining a percentage of 76.2% in the high or good category. this shows that Paper Show is effectively used in learning.